UPAYA MEMPERTAHANKAN AKHLAK GENERASI MILENIAL MELALUI HADIS "HENDAKLAH BERKATA BAIK ATAU DIAM" - Aulia, Mita; Adawiyah, Nely Rubaiah (Dirasa Islamiyya: Journal of Islamic Studies, 2024)
This research aims to examine Efforts to Maintain the Morals of the Millennial Generation Through Hadith, Should You Say Good or Silent. This study uses the method of iteratur, collecting written works and a wealth of reading information sources related to the material. The presentation method uses a qualitative method, namely a description of the problem through words based on theory or concept. The Millennial Generation was born in the century of technological development, so it is not surprising that this generation is very able to adapt to technological developments and use it as a medium of social interaction. This media is a free place for users to disseminate information, so it is necessary to control this freedom, so that they are orderly in using social media in a useful way without anything that disturbs the harmony of life in general and or the rights of other people's lives. Through the hadith "Say good or be silent", we can emulate how the Prophet Muhammad told us to be careful in speaking or commenting. Especially commenting on social media which is currently a tool for the easiest place to spread information.